Macmillan Mathematics Pupil's book 5A - "Broadbent, Paul" (Macmillan Education: Oxford, 2010)
The Pupil$1 (Bs Book A contains units 1-12 and provides a clear explanation of the key steps needed to learn specific skills and concepts, as well as practice, reinforcement and enrichment activities. Students are also taught the correct use of mathematical vocabulary and the accompanying CD-ROM provides further reinforcement and assessment.s
Keywords: Mathematics- Anglais